Financial Stability and Monetary Framework under Interest-Free DSGE Settings for Pakistan - Rao Javaid Iqbal; Atiquzzafar Khan; Hafiz Muhammad Yasin (Islamic Banking and Finance Review, 2023)
Various small and large, conventional and interest-free, DSGE models havebeen developed, simulated, and compared. After a large conventionalmodel, an interest-free NK model was prepared with household preferences,retail firms, and capital-producing firms. The deduction of zakat wassuggested with appropriate incidence. The model was estimated usingquarterly data for Pakistan between 1990 and 2009, a period characterizedby the consolidation of monetary and macro-prudential policies besides theopening up of the banking sector. This large-scale model included financialaccelerator, systemic risk, the inter-bank market, macro-prudential policy,and monetary policy. Both types, that is, interest-based conventional modelsand interest-free models, were estimated and compared. The welfare loss offour conventional and three interest-free models was computed andcompared, where loss decreased with monetary policy and increased withmoney in utility. The lower value of welfare loss for the large conventionalmodel exhibited effective financial stability policies in Pakistan, ascompared to the basic model. It was found that interest-free monetarymodels couldn’t reduce welfare loss, when compared with conventionalmodels. The study also evaluated three interest-free rates of return asalternatives to interest rates theorized by Khan and Mirakhor (1989). It wasfound that the shift towards an interest-free regime for entrepreneurs,banking, inter-bank operations, central banking, and policies can besimulated with Pakistan’s data. The Islamic model showed lesserconvergence, so the fit of the model was reduced.